Implementation and control of high gain of DC/DC boost converters - Toh, Yong Fu (2017)
In this project, the implementation of two high-order boost converter systems are presented. The converters are the quadratic boost converter and the fifth-order boost converter. The controllers for the voltage regulation of the converters are also implemented. The controllers implemented are the non-adaptive and adaptive sliding mode controllers.